Impact Analysis of Sakura School Simulator Game on Language Acquisition of 7-Year-Old Children - Uqba, M Sholih Salimul; Rohmawaty, Evy Nur; Nuzula, Muhammad Firdaus; Wargadinata, Wildana (Journal of Language, Literature and Teaching, 2023)
This study investigates the impact of the smartphone game Sakura School Simulator on language acquisition in 7-year-old girls in Wajak village, Wajak sub-district, Malang district, East Java. It also investigates the understanding of language development in children, including the biological and social aspects that influence the process. The purpose of this study is to understand the extent to which the Sakura School Simulator game can influence language skills in 7-year-old children, with a focus on the use of English. The method used in this study was based on a descriptive qualitative approach and included observation of children playing the Sakura School Simulator game by listening and taking notes. The results showed that children who played the Sakura School Simulator game actively used various English terms in the game, understood instructions in English, and were able to use various game features and options in English. However, the study also warned about the potential negative effects of overusing the game, such as addiction, lack of socialization, and lack of politeness in language use. In conclusion, the use of Sakura school simulator can contribute to language acquisition, especially English in children aged 7 years, but supervision is needed to ensure a positive and effective play experience in children's language development. Keywords: Sakura School Simulator, Language Acquisition, 7 Year Olds